2016
DOI: 10.1377/hlthaff.2016.0012
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Mental Health Care Parity Might Require Changes In Payments And Competition

Abstract: One of the most prominent features of the Affordable Care Act has been the promotion of individual health plans chosen by consumers in the Marketplaces. These plans are subject to regulation and paid by risk-adjusted capitation, a set of policies known as managed competition. Individual health insurance markets, however, are vulnerable to what economists describe as efficiency problems stemming from adverse selection, and Marketplaces are no exception. Health plans have incentives to discriminate against servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Demand response for mental health and substance abuse (MH/SA) services are of intermediate elasticities (−0.26). This may reflect the current trend that most people getting professional mental health treatment are getting drugs only or receiving MH/SA treatment in primary care (McGuire, 2016), which is consistent with the low level of spending on specialty mental health care observed in our data. Surgical procedures and Dialysis, two very expensive types of services, are of the wrong sign and not statistically different from zero.…”
Section: Resultssupporting
confidence: 87%
“…Demand response for mental health and substance abuse (MH/SA) services are of intermediate elasticities (−0.26). This may reflect the current trend that most people getting professional mental health treatment are getting drugs only or receiving MH/SA treatment in primary care (McGuire, 2016), which is consistent with the low level of spending on specialty mental health care observed in our data. Surgical procedures and Dialysis, two very expensive types of services, are of the wrong sign and not statistically different from zero.…”
Section: Resultssupporting
confidence: 87%
“…Previous literature has also demonstrated that mental health and substance use disorders are substantially undercompensated in the current Marketplace risk adjustment system (McGuire ; Montz et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…While further work is needed, I expand the evidence base that policy changes to risk adjustment formulas may be warranted. This could include altering risk adjustment methodology, such as adding HCCs or prescription drug flags to existing formulas (McGuire ; Montz et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to mental health care, even under conditions of ostensible mental health parity, can be complicated further by issues that are difficult to regulate, such as narrow provider networks for those offering mental health services. 38 Considering that 50% of transgender patients in national surveys report that they need to educate their providers about gender minority care, 27 the ''effective'' network of mental health care providers prepared to provide high-quality mental health care to gender minority patients is likely much smaller than that available to the broader population. In focus groups of transgender women living with HIV who also had used mental health treatment, participants ''discussed the need for more readily available mental health services aside from psychotropic medications,'' 39 in particular, because there was a perception that medications were being used more often because they were ''more readily available than therapy, which participants viewed as a problem.''…”
Section: Discussionmentioning
confidence: 99%